Taboo in Balinese Language Spoken in Nusa Penida Based on Tri Hita Karana Concept - Tristiani, Ni Kadek Ita; Budasi, I Gede; Ramendra, Dewa Putu (The Art of Teaching English as a Foreign Language (TATEFL), 2024)
This study aimed at identifying taboo words of Balinese language spoken in Nusa Penida based on the concept of Tri Hita Karana. Descriptive qualitative was used as the research design of this study. There were three of local people in Nusa Penida recruited as the research informants by using purposive sampling technique. The data were collected by conducting interview and taking-note. The instruments were interview guide and note or check-list. The obtained data were analyzed by using qualitative data analysis method consisting of data reduction, data display, and conclusion drawing. The finding showed that there were 60 taboo words of Balinese language spoken by the local people in Nusa Penida Island. It was found that there were eight forms of taboo words spoken by local people in Nusa Penida Island, such as; metaphor, metonymy, and euphemism, abusive, cursing, obscenities, blasphemies, swearing, and expletive. It also discovered that there were 16 categories of references used, such as; parents name, animal name, God name, name of people who have died, name of relatives, mentioning genitals, sexual activity, specific jobs, bodily function, wisdom of ruler, illness, nature, name of spirits, personal pronoun, specific activity.